Investigation of the running-in process in photoinduced superlubricity - Han, Ke; Ma, Pingsu; Ma, Liran; Tian, Yu; Luo, Jianbin (Frontiers in Materials, 2023)
Photoinduced superlubricity on TiO2 surfaces is a newfound phenomenon which draws researchers’ attention. It provides a new method to achieve superlubricity (COF<0.01) with an external light field. However, photoinduced superlubricity can only be realized under specific conditions. Improper running-in conditions, such as speed, load and pH value will lead to failure of superlubricity even after ultraviolet illumination on the TiO2 surface. In this paper, the worn surfaces after running-in in sulfuric acid solution and testing in 70% v/v glycerol aqueous solution were investigated thoroughly. Results reveals that the morphology of worn scars differs under different running-in process. While the running-in speeds and loads are low (<0.03 m/s and <2 N), the surface of the TiO2 will not be polished adequately which leads to failure of superlubricity with or without ultraviolet illumination. While the running-in speeds are large enough (> 0.1 m/s) to reduce the roughness of the worn areas, the elastohydrodynamic effect dominates the lubrication and the adsorbed lubricant molecules induced by ultraviolet illumination have little help to the lubrication. However, when the loads are large enough (> 9 N), the corresponding contact pressure will be too large to form lubricate film and superlubricity will fail since the boundary lubrication dominates. When the pH value of running-in solution is lower than 4.5, photoinduced superlubricity is easier to achieve due to the formation of SiO2 layer on the Si3N4 ball and better attraction to lubricant molecules with hydroxyl on TiO2 surface. Anyhow, the ultraviolet illumination can reduce the friction coefficient of the TiO2/Si3N4 tribological system, and can realize photoinduced superlubricity under appropriate running-in conditions.